Neil Armstrong the first man on the moon - Byers, Ann (New York : Rosen Pub. Group, 2004)
Discusses the life and training as an astronaut of Neil Armstrong, the first man to set foot on the moon.
8 - 10 years
Keywords: Armstrong, Neil -- 1930-; Astronauts -- United States -- Biography; Astronauts